Dental caries, gingivitis, and oral health practices in 6-12-year-old children with autism spectrum disorder: prevalence and risk factors - Phu, Tran Xuan; Loi, Nguyen Hong; Hao, Tran Kiem; Son, Nguyen Huu; Tam, Nguyen Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental condition affecting communication and behavior. The prevalence and risk factors for oral diseases in Vietnamese children with ASD remain unclear. The study aimed to assess the prevalence and risk factors associated with dental caries, gingivitis and oral care practices among 6–12-year-old children with mild-to-moderate ASD. Methods: A cross-sectional study was conducted on 218 schoolchildren with ASD, diagnosed per DSM-5, in Hue, Vietnam. Oral health was evaluated using the dental caries index (DMFT), gingivitis index (GI), calculus index (CI), and plaque index (PI). A pre-designed questionnaire assessed children’s oral care practices via parent/caregiver interviews. Logistic regression identified risk factors for dental caries and gingivitis. Results: Caries prevalence was 80.3%, with 70.2% in permanent and 77.1% in deciduous teeth. The mean (standard deviation) dmft and DMFT were 6.1 (4.3) and 3.1 (3.2), respectively. Gingivitis was present in 79.4% of participants, with 62.9% classified as mild and 16.5% as severe. Children with gingivitis and poor oral care practice, including lack of flossing, absence of fluoride mouthwash at school, frequently sugary food consumption, food-grinding habit, self- brushing, had significantly higher odds of developing dental caries. Male with plaque and gingivitis, combine with poor oral care practice (not use dental floss, frequently consumed sugary foods, had food-grinding habit, and practiced self-brushing) had significantly higher odds of developing gingivitis. Conclusions: The prevalence of dental caries and gingivitis was high in the study population. Risk factors included current gingivitis and inadequate oral care practices.